Scalp microneedling as a complementary therapy for female pattern hair loss - Pedro Colli Rocha Dias; Hudson Dutra Rezende (Sociedade Brasileira de Dermatologia (SBD), 2022)
Female pattern hair loss (FPHL) is one of the most frequent complaints in dermatological practice. It affects up to 50% of climacteric and postmenopausal women. Despite multiple therapies available nowadays, some patients are refractory to conventional treatments, requiring the association of second-line therapies to obtain good aesthetic results. This paper aims to show the advantages of microneedling of the scalp for such cases by reporting the case of a 48-years-old patient who failed to the association of topical minoxidil and oral finasteride therapy.